Targeted radionuclide therapy in endocrine-related cancers: advances in the last decade - Al-Toubah, Taymeyah; Strosberg, Jonathan; Hallanger-Johnson, Julie; El-Haddad, Ghassan (Frontiers in endocrinology (Lausanne), 2023)
Targeted radionuclide therapy plays an increasingly important role in managing endocrine-related tumors and significantly advances the therapeutic landscape for patients with these diseases. With increasing FDA-approved therapies and advances in the field, come an increased knowledge of the potential for long-term toxicities associated with these therapies and the field must develop new strategies to increase potency and efficacy while individualizing the selection of patients to those most likely to respond to treatment. Novel agents and modalities of therapy are also being explored. This review will discuss the current landscape and describe the avenues for growth in the field currently being explored.